Áreas protegidas e ambientes urbanos:Novos significados e transformações associados ao fenômeno da urbanização extensiva / Protected Areas and Urban Environments: new meanings and changes associated with the phenomenon of extensive urbanization - Altair Sancho; José Antonio Souza de Deus (Sociedade & Natureza)
This paper proposes to discuss the relationship between actions of nature protection and urban environments, with attention to the influences of the phenomenon of extensive urbanization in the dynamics of territories permeated by protected areas. It is postulated that this interrelationship not only refers to the origin of the movement to create spaces for nature conservation, but also interferes in its constitution, especially in countries like Brazil, where many of these areas were implanted near urban centers. Faced with the new socio-spatial and organizational configurations observed in the metropolis in recent decades, we call attention to the phenomenon of extensive urbanization, a term proposed by Monte-Mór to interpret the movement of extension conditions and urban ways of life beyond the limits of the metropolis. The unifying character of this movement and the pressures on the border has been responsible for reframing the rural-urban relationship, broadly, with direct repercussions on territorial dynamics of protected areas located in the coverage of metropolitan centers. As a result, there is a complexity of the senses and meanings attributed to protected areas and the appearance of several challenges to the purposes of biodiversity conservation and promotion of territorial development.